Programming Wireless Sensor Networks with the TeenyLIME Middleware - Costa, Paolo; Mottola, Luca; Murphy, Amy L.; Picco, Gian Pietro (The 8th ACM/IFIP/USENIX International Middleware Conference (Middleware'07). Newport Beach (CA, USA). November 2007., 2007)
Wireless sensor networks (WSNs) are evolving to support applications, where actuators are physically interspersed with the sensors that trigger them. This solution maximizes localized interactions, improving resource utilization and reducing latency w.r.t. solutions with a centralized sink. Nevertheless, application development becomes more complex: the control logic must be embedded in the network, and coordination among multiple tasks is needed to achieve the application goals. This paper presents TeenyLIME, a WSN middleware designed to address the above challenges. TeenyLIME provides programmers with the high-level abstraction of a tuple space, enabling data sharing among neighboring devices. These and other WSN-specific constructs simplify the development of a wide range of applications, including sense-and-react ones. TeenyLIME yields simpler, cleaner, and more reusable implementations, at the cost of only a very limited decrease in performance. We support these claims through a source-level, quantitative comparison between implementations based on TeenyLIME and on alternative approaches, and by analyzing measures of processing overhead and power consumption obtained through cycle-accurate emulation.